KOMPETENSI PENYULUH DALAM MENGAKSES INFORMASI PERTANIAN (KASUS ALUMNI UT DI WILAYAH SERANG) - Huda, Nurul; Setijorini, Ludivica Endang (LPPM Universitas Terbuka, 2010)
The objectives of this study were to describe the competence of the agriculture extension workers in terms of their access on agricultural information. By using an explanatory research design and a census method, all population of agricultural extention workers in Serang Regency, West Java were used as respondent. Data were collected by questionnaire and analyzed with descriptive and regression analysis. The results of this study indicated that generally no relation was found between factors on individual characteristics, learning activities at UT, other learning source, environment factors, and their competence on information access. It was found that their competence level was categorized as moderate. The same level was also on their competence aspects, those were cognitive, affective, and psychomotor. Related to their perfomance in innovation implementation, the findings indicated that the level was moderate. In conclusion, the competence of agriculture extension workers which was categorized as moderate need to to be improved in order to give a better service to farmer.